Rethinking Masculinities and Narratives of Wartime Sexual Violence: A Gender Analysis of Sexual Violence Against Men in the Democratic Republic of the Congo, El Salvador, and Iraq. - Jencik, Lauren. (Tufts Archival Research Center, 2017)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Wartime sexual violence is a known and heavily researched issue in both academia and policy. However, a growing body of research shows that, despite acknowledgement of men and boys as victims of wartime sexual violence, responses remain biased towards women and girls, often rendering male victims silent. This silence calls into question multiple factors including narratives of wartime sexual violence and perceptions of gender, and masculinities in particular. Thus, this paper will address the question: how do constructions of masculinity affect narratives and perceptions of wartime sexual violence against men? To answer this question, this paper will examine three case studies in which the use of wartime sexual violence against men varies in scope and context: The Democratic Republic of the Congo (DRC), El Salvador during its Civil War, and the United States Army in Abu Ghraib during the Iraq War.